Differences in the Distribution of Peripheral Blood Leukocyte and Lymphocyte Subsets in Pulmonary Tuberculosis Patients - Carneiro, Valdirene Leão; Donato dos Santos, Rosalina Guedes; Sampaio, Geraldo Pedral; Casela, Marilda; Netto, Eduardo Martins; Nascimento, Roberto José Meyer; Freire, Songeli Menezes (Revista de Ciências Médicas e Biológicas, 2014)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Introduction: It has been suggested that individuals exposed to Mycobacterium tuberculosis can eliminate the infection through the innate immune response without the participation of the acquired immunity. However, T helper type 1 immune response is critical to control persistent infection. Objective: The purpose of this study was to evaluate the distribution of leukocyte and lymphocyte subsets in peripheral blood of individuals with pulmonary tuberculosis (TB) and positive Tuberculin Skin Test (TST). Methodology: In order to achieve that goal, we have collected blood sample from thirty-four treatment-naïve TB patients, fifty TST-positive and forty-one TST-negative individuals. Results: The evaluation has shown a significant reduction in the number of total lymphocytes, B cells, CD4+ and CD8+ T cells and percentage increase of NK cells, neutrophils and monocytes in TB patients, when compared to TSTpositive and TST-negative individuals. There was no statistical difference for leucocyte and lymphocyte subsets between TST-positive and TST-negative groups. Peripheral blood white cell counts change significantly at diagnosis. Conclusion: The quantification of these cells may support the diagnosis and monitoring of patients with pulmonary tuberculosis. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>